Dengue Vaccines: Challenge and Confrontation - Perng, Guey C.; Lei, Huan-Yao; Lin, Yee-Shin; Chokephaibulkit, Kulkanya (Scientific Research, 2011)
Dengue has been recognized as one of the most important vector-borne human diseases. The disease is induced by dengue virus infection resulting from the bite of an infected Aedes spp. mosquito after imbibing the tainted blood from animals or patients. Dynamic clinical spectrums ranging from asymptomatic, undifferentiated fever, typical dengue fever (DF), dengue hemorrhagic fever (DHF) and dengue shock syndrome (DSS) have been well documented. Initially, the disease was mainly restricted in tropical and subtropical zones. However, with factors such as ineffective vector control, frequency of human migration, unplanned urbanization, and changing climate temperature, the disease has been spotted at almost every territory of the earth. Dengue has been associated with human disease for more than two centuries. Although classic DF is viewed as a self-limited illness, subjects normally resolve within two weeks and recover without any noticeable complications or sequelae, some of these infected individuals may progress to lifethreatening DHF/DSS, characterized with plasma leakage due to an increase in capillary permeability. The significantly increased public health threat and the burden of morbidity and mortality of dengue globally has caught the attention of public officials and prompted an action to find a way to contain and prevent the disease. The lack of specific dengue therapeutics has led to an emphasis on vaccine development, one of the best and effective strategies to reduce and prevent the illness. Making a dengue vaccine has been attempted more than six decades; although some of these products are in clinical trials, vaccine development for the prevention of dengue disease is still at its infancy. So far no dengue vaccine is available for the public. Dengue vaccine development may be hindered by the complexity of the clinical presentations, which implicates that multiple pathogenic mechanisms are involved in dengue disease. Some of these elements will be discussed in the current review. Opening up discussion on these pros and cons and engaging in more research to understand these features would not only improve the understanding of the pathogenesis of the dengue virus infection but also pave a new tactic to develop a safer and effective dengue vaccine
Keywords: Flavivirus; Dengue Fever; DHF; Dengue Vaccine